2018
DOI: 10.1177/1747493018816511
|View full text |Cite
|
Sign up to set email alerts
|

Low flow in the left atrial appendage assessed by transesophageal echocardiography is associated with increased stroke severity—Results of a single-center cross-sectional study

Abstract: Background: About 25% of strokes are thought to be cryptogenic. There is growing evidence that most of these cryptogenic strokes are thromboembolic and caused by an undetected atrial fibrillation. Measured slow flow in the left atrial appendage has been proposed to be an indicator for the thromboembolic risk since it is possibly associated with undetected atrial fibrillation. Methods: We evaluated all patients (n ¼ 909; mean of 62 years, 39% female) admitted with an ischemic stroke (84%) or transient ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The left atrial appendage was proved to be a major source of emboli responsible for cardioembolic stroke in previous studies [ 24 ], and decreased LAAV has been proved to be a well-recognized risk factor for left atrial appendage thrombosis and stroke [ 6 , 24 , 25 , 26 ]. In clinical practice, TEE was regarded as the first technique of choice to measure the function of left atrial appendage, but TEE may cause severe discomfort in patients and, moreover, serious complications (such as esophageal damage) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The left atrial appendage was proved to be a major source of emboli responsible for cardioembolic stroke in previous studies [ 24 ], and decreased LAAV has been proved to be a well-recognized risk factor for left atrial appendage thrombosis and stroke [ 6 , 24 , 25 , 26 ]. In clinical practice, TEE was regarded as the first technique of choice to measure the function of left atrial appendage, but TEE may cause severe discomfort in patients and, moreover, serious complications (such as esophageal damage) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even patients with low CHA 2 DS 2 -VASc score may suffer a stroke. The score also fails to take into consideration the structure ( 31 , 115 ) and the hemodynamic characteristics for the LAA ( 37 , 116 , 117 ) in addition to other clinical markers ( 118 120 ). Thus, additional LAA features and clinical markers may further risk stratify stroke prevention for patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…Among 721 patients who underwent transesophageal echocardiography in a post hoc analysis of the Stroke Prevention in Atrial Fibrillation-III trial, reduced LAA flow velocity (<20 cm/s) was associated with thrombus formation and subsequent cardioembolic stroke (33). Similarly, a cross-sectional study of 909 stroke patients with or without AF found that decreased LAA flow velocity (<60 cm/s) was associated with clinically elevated stroke severity (34), and an observational study of 786 patients with cryptogenic stroke found that decreased LAA flow velocity on transesophageal echocardiography was associated with multiple infarcts (35). These results indicate that decreased flow velocity in the LAA is an additional risk factor for cardioembolic stroke, regardless of whether AF exists.…”
Section: Hemodynamic Markersmentioning
confidence: 99%